The Message Matters : The Economy and Presidential Campaigns - Vavreck, Lynn, 1968- (Book collections on Project MUSE., 2009)
The economy is so powerful in determining the results of U.S. presidential elections that political scientists can predict winners and losers with amazing accuracy long before the campaigns start. But if it is true that "it's the economy, Stupid," why do incumbents in good economies sometimes lose? The reason, Lynn Vavreck argues, is that what matters is not just the state of the economy but how candidates react to it. By demonstrating more precisely than ever before how candidates and their campaigns affect the economic vote, The Message Matters provides a powerful new way of understanding pa.